2006
DOI: 10.1097/00043426-200606000-00008
|View full text |Cite
|
Sign up to set email alerts
|

POG 8625: A Randomized Trial Comparing Chemotherapy With Chemoradiotherapy for Children and Adolescents With Stages I, IIA, IIIA1 Hodgkin Disease

Abstract: To determine if 6 courses of chemotherapy alone could achieve the same or better outcome than 4 courses of chemotherapy followed by radiation therapy (chemoradiotherapy) in pediatric and adolescent patients with Hodgkin disease. Children < or =21 years old with biopsy-proven, pathologically staged I, IIA, or IIIA1 Hodgkin disease were randomly assigned 6 courses of alternating nitrogen mustard, oncovin, prednisone, and procarbazine/doxorubicin, bleomycin, vinblastine, and dacarbazine (treatment 1) or 4 courses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 33 publications
3
35
2
2
Order By: Relevance
“…29 However, these are minor points, as the direction of the effect is clear and only the magnitude may vary slightly. Again, the trials included in the sensitivity analyses 20,[34][35][36][37][38] also supported the results in favor of CMT. Three trials had effect estimates favoring CMT, two trials observed no deaths 34,36 and only one trial 20 observed a slight effect favoring chemotherapy alone, which was not statistically significant.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…29 However, these are minor points, as the direction of the effect is clear and only the magnitude may vary slightly. Again, the trials included in the sensitivity analyses 20,[34][35][36][37][38] also supported the results in favor of CMT. Three trials had effect estimates favoring CMT, two trials observed no deaths 34,36 and only one trial 20 observed a slight effect favoring chemotherapy alone, which was not statistically significant.…”
Section: Discussionsupporting
confidence: 57%
“…20,[34][35][36][37][38] When including all of these trials into a meta-analysis for tumor control, the HR was 0.38 (95% CI 0.28 to 0.51). When restricting the analysis to the trials that kept the number of cycles the same between the group that received radiotherapy and those that did not [34][35][36][37] the HR was 0.39 (95% CI 0.27 to 0.55).…”
Section: Tumor Controlmentioning
confidence: 99%
See 3 more Smart Citations